2004
DOI: 10.1093/bja/aeh136
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in advancing a tracheal tube over a fibreoptic bronchoscope: incidence, causes and solutions

Abstract: Fibreoptic tracheal intubation is a useful technique in patients whose tracheas are dif®cult to intubate. 66 69 However, there are two major dif®culties with this technique. The ®rst is location of the glottis and insertion of a ®brescope into the trachea. Induction of general anaesthesia (with or without neuromuscular block) causes the soft palate, tongue and epiglottis to approximate to the posterior pharyngeal wall, 64 and thus little air space is left in the oropharynx for manoeuvring the tip of the ®bresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
209
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(213 citation statements)
references
References 85 publications
2
209
1
1
Order By: Relevance
“…The merit of this device is that it may reduce the chance of hold-up at the cross bars of the LMA Classic [7] as the AIC fits snugly over the fibrescope. In addition, railroading the tube over the AIC is likely to be easier than when using a fibrescope alone because of the greater external diameter of the AIC and consequent reduction of the gap between an AIC and a tracheal tube [8]. A 2009 survey of all anaesthetic department in the UK (64% response rate) found that only 50% (87 ⁄ 175) of the departments had the AIC available for use (Evans H, Hodzovic I, Latto IP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The merit of this device is that it may reduce the chance of hold-up at the cross bars of the LMA Classic [7] as the AIC fits snugly over the fibrescope. In addition, railroading the tube over the AIC is likely to be easier than when using a fibrescope alone because of the greater external diameter of the AIC and consequent reduction of the gap between an AIC and a tracheal tube [8]. A 2009 survey of all anaesthetic department in the UK (64% response rate) found that only 50% (87 ⁄ 175) of the departments had the AIC available for use (Evans H, Hodzovic I, Latto IP.…”
Section: Discussionmentioning
confidence: 99%
“…This device is likely to reduce the chance of hold-up of the AIC at the cross bars of the LMA Classic [7] as it fits snugly over the fibrescope. In addition, railroading the tube over the AIC is likely to be easier than when using a fibrescope alone because of the greater external diameter of the AIC and consequent reduction of the gap between the AIC and the tracheal tube [8].…”
mentioning
confidence: 99%
“…The fiberoptic bronchoscope is regarded as the most reliable tool for nasotracheal intubation, but considerable skill and knowledge are required to achieve a smooth tracheal intubation [5,6]. In addition, its routine use may be impractical, partly because of the high cost of purchasing and maintaining the device.…”
Section: Methods Of Nasotracheal Intubationmentioning
confidence: 99%
“…[6] There was also a failure in fiber-optic intubation on two separate occasions. [7] We decided to do a conventional laryngoscopy without cervical extension and documentation of Cormack-Lehane score, as this patient is likely to come for further surgeries, due to the visualization Cormack-Lehane III of the vocal cords the patient was intubated.…”
Section: Case Historymentioning
confidence: 99%